Penetapan X-Banner , Spanduk Dan Kartu Nama Sebagai Media Promosi - Satriya Budi Septianto; Erlangga Saputra (Switch : Jurnal Sains dan Teknologi Informasi, 2023)
Current technological developments have greatly influenced developments in the business world with the ease of using technology, especially information technology, which has succeeded in moving the economy and trade, the ease of communication technology makes it easier to carry out trade transaction activities not only for one region but trade can now be carried out between cities , province, between islands or between countries. Such trade transactions require shipping services to deliver products from producers to consumers, this is what many companies then use by providing goods delivery services or what is often called expeditions.